Pengaruh Keselamatan dan Kesehatan Kerja (K3) Terhadap Kenyamanan Bekerja dengan Motivasi Sebagai Variabel Moderasi Pada PT. ASDP Indonesia Ferry (Persero) Sibolga - Listy Sandrina Lumban Gaol; Robinhot Gultom; Winarto Winarto (Universitas Methodist Indonesia, 2024)
The purpose of this study was to determine the effect of Occupational Safety and Health on the Convenience of Working with Motivation as a Moderating Variable at PT. ASDP Indonesia Ferry (Persero) Sibolga. The population in this study were all employees, totaling 35 employees. Sampling using saturated sample technique, with a total sample of 35 people. The analysis technique used is a statistical test through regression test, t-test, MRA (Moderated Regression Analysis) and the coefficient of determination R-Square (R2). The results of this study indicate that Occupational Safety and Health has a partial and significant effect on the comfort of working at PT. ASDP Indonesia Ferry (Persero) Sibolga. However, motivation has not been able to moderate the relationship between Occupational Safety and Health (K3) on the comfort of working at PT. ASDP Indonesia Ferry (Persero) Sibolga, where the results of the t-test were lower than the direct relationship 4.259 < 4.673, it can be concluded that motivation weakens the relationship between occupational safety and health on the comfort of working at PT. ASDP Indonesia Ferry (Persero) Sibolga.